Evaluation of the Comparative Effectiveness of Fiscal Measures and Supply Chain Strategy at Stimulating Oil Production from 2010 to 2016 Carried Out with the ï¥-KAM Mathematical Model - V.V. Ponkratov; A.K. Karaev; A.I. Masterov; S.V. Anureev; A.S. Lozhechko (International Journal of Supply Chain Management, 2019)
The article evaluates the effectiveness of measures of supply chain management and national fiscal policies aimed at stimulating oil production in several countries (the USA, Canada, Brazil, Norway and Russia). Calculations were carried out with the ï¥-KAM mathematical model using the data for the period from 2010 to 2016. The model includes the following: the input indicators are budget transfers and tax benefits for oil producers, and the output indicators are the average annual volumes of oil production. Regarding the price efficiency of fiscal policy aimed at stimulating oil production in 2010â€“2016, Russia showed the lowest result. At the same time, Russia demonstrated the highest efficiency of using budget transfers to stimulate oil production, and Canada achieved the greatest efficiency in applying tax measures.